L’Estremo Oriente di Djemil Anik. Influssi e interpolazioni delle danze giavanesi nell’attività artistica e pedagogica - Fiorella Cardinale Ciccotti (Danza e Ricerca)
Questioning the topic of métissage within the French interwar context, the author of the essay aims to investigate the career of the dancer Djemil Anik (1888-1980) – of French-Malay origins and an expert in Javanese female court dances – starting from her first debut at the Théàtre des Arts in Paris until the full affirmation of her pedagogical activity. Starting from the historical-critical analysis of the first solos, the paper depicts the strategies she implemented to address the cultural mutations linked to the sharpening of contemporary ethnographic consciousness, which include trips to Java for field research and a theoretical and pedagogical approach that aims at hybrid education.